Store atmosphere: Comparing super and hypermarket customer perception - Cameira, Rita Margarida Melo Proença (2009)
In the competitive market that we live in, managers need to be empowered with the right tools to use in order to turn their business into an outstanding one. In the retail market, especially in a recession situation, price cannot be the only battle tool. The service and environment that each store provides to its customers can be used to create a unique combination, offering customers with a specific formula that they will not find anywhere else. But does a specific formula based on environment variables have the same perception effect on super and hypermarket customers? Does the store format influence the atmosphere perception when the same elements are used? This study aims to pursue this issue and provide some insights into which of the interior atmospheric variables are not sensitive to store format.